Effects of six weeks of plyometric training on the ground vs on a mini-trampoline on strength, jump performance, and balance in male basketball players—randomized clinical trial - Villalba, Marina M. [UNESP]; Eltz, Giovana D. [UNESP]; Fujita, Rafael A.; Panhan, Ana C.; Cardozo, Adalgiso C. [UNESP]; Gonçalves, Mauro [UNESP] (Springer Nature, 2022)
Purpose: To compare the effects of a 6-week plyometric training protocol performed on the ground or a mini-trampoline on basketball players' strength, jumping, landing, and balance. Methods: This randomized clinical trial recruited 30 male basketball athletes, (17–21 years), were divided into three groups: plyometric training on the mini-trampoline group (MT) (n = 11), plyometric training on the ground group (GR) (n = 9), and control group (CON) (n = 10). Isometric strength, countermovement jump height, landing impact (ground reaction force) in single-leg drop landing jump, and balance [center of pressure (COP) Area, COP length] in single-leg standing tests (eyes closed and open) were evaluated before and after intervention performing a MANOVA with repeated measures (pre- and post-training) for each dependent variable. Results: No statistical effects were found for strength and jump height for any group or moment. In the single-leg drop landing, GR and CON showed lower landing impact than MT (p < 0.001). For the COP area with eyes open, GR showed better results after training (p =.013), and MT showed worse results (p < 0.001). Regarding COP area with eyes closed, all groups demonstrated improvements (p = 0.001). Regarding the COP length with eyes open, interactions showed differences between all groups, but not for moments pre- and post-training (p = 0.37). Improvements in COP length with eyes closed were observed post-training for all groups (p = 0.041). Conclusion: To improve landing during jumps and balance performance, coaches should tend toward conventional plyometric training rather than on a mini-trampoline.
Keywords: Athletic performance; Plyometric exercise; Resistance training; Sports training